hw5sol

# hw5sol - 5%. £7 W) # S’ 14. Note the transform pair. 3...

This preview shows pages 1–5. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 5%. £7 W) # S’ 14. Note the transform pair. 3 52+4 cos 2: <-+ By Proposition 2.12, s——1 6t COS 216-) Hence, ~ _1 4(s—1) M‘ﬁ {(s—1)2+4} _ —1 __§;1___ "M {(s—1)2+4} =4e’c052t. 18. Let £(y) = Y(s). Since y(0) = O, and y’(0) = —-1, £01" a y' — 2y) = szY(s)+1-« sY(s) — 2Y(s). In addition, 2 (s —2)3‘ [,(tzeZ‘) = Solving (sz—s—2)Y(S)+1= 2 (S~2)3 for Y, we get V/ \ *1 | 2 1 \S} —— . T 7 ' ' (5 +1)(s * 2) (S +1)(S ~ 2)4 Tho farmn A“ «Inn 1‘ n-lnf ka‘ 9 Annnmnnmhnng lllv [8.11.1113 U1] “1U llglll ll VV “UVUILIFUDJUUA —1 1/3 1/3 and 2 2/81 2/81 2/27 f : ——-“" " + 2 2 <s+n(s—2)4 s+1 3‘2 ‘3”) 2/9 + 2/3 ‘ (s~2)3 9—94 Therefore, 29/81 29/81 2/27 Y(s)=s+1—s_2 (3—2)2 9 2 3 _ .91.. + / 36. Find a partial fraction decomposition S (s + 2)2(s2 + 9) A B Cs + D + ._.___ s+2 (s+2)2 + s2+9 Equating numerators s = A(s + 2)(s2 + 9) + 3(32 + 9) + (Cs + D)(s + 2)2 = (A+C)s3+(2A+ B+4C+D)s2 + (9A +4C+4D)s + (18A +93 +40) Thus, A+C=0 2A+B+4C+D=0 9A+4C+4D=1 18A+93+4D=0 and A = 5/169, B = —2/13, C = ~5/169, and D 2 36/169. Thus, _ 5/169 ~2/13 y(t) =5 1{ + s + 2 (S + 2)2 ——(5/169)s 36/169} + M. s2 + 9 + 52 + 9 , Note the transform pair. [95. By Proposition 2.12, 1 —21 t . e ‘9 (s+2)2 Thus, 5 -2t 2 —2t 5 12 ' :_ _._ ___ 3t —— 3t. W) 1696 13“ 169COS +169sm 8. Let C(y) = Y. Then £0" — 2y) = £(e"’ cost). Note the transform pair. s cost <—> s2+1 Then by Proposition 2.12, “ cost 4+ S +1 e -+—————~. (5 +1)2 +1 Thus, 5 +1 L ’ — 2L? = (y) (y) (5+1)2+1 3 +1 ~ Y ~ 0 '— 2Y = s (s) y<> (s) Mm“ But y(0) = —2, so 3 +1 ~ 2 Y 2 = —-————~— (s )(s)+ (S+1)2+1 *2 s +1 Y(s) = s—2+ ((s+1)2+1)(s—2)' Find a partial fraction decomposition. s+1 _ A + Bs+C (3—2)((s+1)2+1)_s-—2 (s+1)2+1 Equating numerators, 5+1=A((s+1)2+1)+(Bs+C)(s—2) =(A+B)s2+(2A—-ZB+C)S +(2A—2C) Thus, A+B=0 2A—ZB+C=1 2A—2C=1, and A = 3/10, B = —3/10, and C 2 ~1/5. Thus, “2 + 3/10 w (3/10)s —1/5_ 5—2 5—2 (s+1)2+1 _ —17/10 —(_3/10)s — 1/5 — ,s—2 + (s+1)2+1 Y(s) = Note the transform pairs 5 s2+1 1 32+1 COSI 6 sint <—> \$3: ,9? and 29 29 2 t : ——— ‘t ._.. ._ 2’ 21‘ y() 81c 81e +—-27te 1 2 2: 1 3 2 _ ._t _ t 9 e + 92‘ e ‘ Proposition 2.12 provides 1 e" cost <-> L (s + 1)2 + 1 1 e“ sint <—> ————~———. (s +1)2 +1 32. (a) Let y = e". Then, y//+4y : 0 rze" +4e" = 0 r2+4 :0. Thus, r : iZi leads to the independent solu- tions y = cos 2t and y :2 sin 2t. Therefore the general solution is 3’1: = C1 COSZt + C2 sin2t. (b) We examine z” + 4g 2 2ei3t. Let z = AeiBt- Then z, = 3Aiei3’ and Z” ._ _9Aei£ and _9Aei3t + 4Aei3t : 2ei3t —9A+4A=2 -—5A=2 A=_3 5 Thus, 2,, = (—2/5)ei3' and the real part of zp IS a solution of y” + 4y = 2 cos 31‘. Thus, 2 = —— cos 3t. )7}; 5 (c) The general solution and its derivative are 3’ = )7]: + y p = C1C082t +Czsin21—gcos3t y’ = —~2C1 sin 2t + 2C2 cos 2t + 2 sin 3!. Thus 7 J’(O)=1=>C1-—:-= y'(0)=—1=>2C2 = *1. Therefore C] = 7/5 and C2 = ~1/2 and the solution is 7 l . 2 y = ECOSZI — istt ~ 300831. ((1) Let My) 2 Y(s). Since y(0) = 1 and ya» = —1, £(y’l + 4y) 2 Y(s)(s2 + 4) — 3 +1. In addition 2.3 s2+9’ £(2 cos 3t) = SO Y(s)(s2 +4) —s +1 = 32 + 9. Solving for Y, we get s — 1 + 23 52 +4 (s2 ~l-4)(s2 + 9)' The fraction on the right has decomposition 2s _ (2/5)s _ (2/5)s (521%)“2 +9) “3 s2 +4 s2 +9' Y(s) = 515 Therefore, (7/5)s —1 a 2/SS n3)— 32+4 s2V+9 7 s 1 2 _ 3 ‘ 32 + 4 2 s2 + 4 5 s2 + 9 and y(t) = COS 2! w ésin 2t .— gcos 3t. 8. We have 3 2t 3” + 3” cos t.— cos 2 2 3t 37: OS 3:1 : -— *— C .- cos 2 2 ' 3t 3” sin 3” Sm 2 2 3n = ' 31‘ -—~ ﬂ sm( 2 ) . II = sin 3 (t a a) . Therefore, H(t—%)cos3z=H(r—%)sin3(t—g). Because f (t) = sin 3t has transform 3 s2 + 9’ then g(t) = H(t —7r/2) sin 3(t ~7r/2) has transform G(s) = (gem/2%) Fm = 3 v ~7r3/2 e s2 + 9 3e—ns/2 : a2 ! n 0 T7 20. Note the transform pair . 2 f(t) = s1n2t <—> F(s) = 32 +4. 24. A partial fraction decomposition. Then, s—0=>‘A~1 " ‘4 s-2:>C-I ’2 s—1=>B- 1 — 4 and 8—5 e—s e—s 6—; Note the transform pairs: 1 f(t)=1<->F(S)=; g(r) 2 32‘ <—> 0(5) 2 1 s —2 __ 2: ﬂ 1 k(t) _ te <—-> K(s) _ (S _2)2. Thus, *1 i 6‘3 ‘ ‘3 1mm —2>2 } ‘0 _ ~1 —-s _1__ 1 “I: [e [43 4(s—2) -u\ l .. + 2(s — 32””) = ﬂme—Smnm — £“l{e"sG(s)}(t) + 2£—1{e“sK(s)}(t)] 1 = Z[H(t—1)f(t— 1)-— Ha — 1>g<r — 1) + 2H(t — 1)k(t — 1)] = ﬂaw — 1) — H(t — Dem—1) + 2H(t—1)(t—— new—D] _l _ _§ _ 20—1) —4H(t 1) 4110 De 1 + 5H0 — 1)te2(’“1) g? 18. Note the expression 1 __ 1 _~ 1 1 S2—3S ~s(s—3) — s 's—3’ = F(s)G(s). We have the transform pairs F(s) = % <==> f(t) = 1, 0(5) = 1 <==> g(t) = e3’. s — 3 Thus, 5‘ l 2 1 }<0 = £‘1{F(s)G<s>}<t), 5 —3s = f * g0), 33 g 3% g x 35 g 28. We start by computing the impulse response function e(t). y" + 5y' + 4)’ = 30?). y(0) = y'(0) = 0 By Theorem 6.10, 1 1 13(3) = ___« = 1 = P(s) s2 +55 +4 (s +4)(s +1) —1/3 1/3 " 5 +4 + s +1' Thus, 1 1 e(t) = -—§e"4‘ + 3e”’, and the derivative is 1 III, :_ —4t____ ——l e ( ) 3e 33 From Theorem 7.16, the solution to y” + 5)” + 4y = g0), y(0)=1, y’(0) = 0 is W) = e * 80) + ayoe’(t) + (ayl + byo)e(t), = e * g0) + (1)(1)e'(t) + [(1)(0) + (5)(1)]e(t)9 = 6 >1: g(t) + e’(t) + 5e(t), ...
View Full Document

## This note was uploaded on 01/12/2010 for the course MATH 53 at Stanford.

### Page1 / 5

hw5sol - 5%. £7 W) # S’ 14. Note the transform pair. 3...

This preview shows document pages 1 - 5. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online